Nuclear eDNA metabarcoding primers for anthozoan coral biodiversity assessment - McCartin,Luke; Saso,Emma; Vohsen,Samuel A.; Pittoors,Nicole; Demetriades,Penny; McFadden,Catherine S.; Quattrini,Andrea M.; Herrera,Santiago (PeerJ, 2024)
The distributions of anthozoan corals are undercharacterized due to their wide bathymetric ranges, occurrences in remote locales, and difficulties of identification from morphology alone. Environmental DNA (eDNA) sequencing promises to be a noninvasive strategy to complement conventional approaches for mapping and monitoring the distribution and biodiversity of coral communities. Primers for eDNA metabarcoding have been designed to amplify nuclear and mitochondrial DNA barcodes in shallow scleractinians and mitochondrial MutS in deep-sea octocorals. However, a comprehensive method for eDNA metabarcoding of all anthozoan corals, including black corals, has not been developed. We leveraged a sequence database of global coral collections, from shallow water to the deep sea, to design new PCR primers for coral eDNA sequencing that target the 28S rRNA gene (28S rDNA). We tested the performance of these primers by amplifying and sequencing eDNA from water samples collected in the Gulf of Mexico near mesophotic and deep-sea corals that were also imaged, sampled, and sequenced. Sequencing libraries produced using the primers were highly enriched in eDNA from octocorals, black corals and scleractinians, with up to 99.9% of the reads originating from these corals. Further, the 28S barcode amplified using the primers distinguished coral genera and species in many cases, like previously developed methods that target eDNA in only octocorals or scleractinians. We recovered amplicon sequencing variants (ASVs) identical to DNA barcodes derived from Sanger sequencing and genome skimming of corals sampled at the same field sites. This new eDNA metabarcoding strategy permits targeted eDNA sequencing of black corals, octocorals, and scleractinians at sites where they co-occur and expands our current toolkit for mapping and monitoring coral communities in shallow coral reefs and the deep sea.
Keywords: Environmental DNA; Biodiversity; Antipatharia; Scleractinia; Octocorallia; Ribosomal DNA